Effects of omega-3 polyunsaturated fatty acid intake in patients with chronic kidney disease: Systematic review and meta-analysis of randomized controlled trials. Issue 2 (February 2020) - Saglimbene, Valeria M.; Wong, Germaine; van Zwieten, Anita; Palmer, Suetonia C.; Ruospo, Marinella; Natale, Patrizia; Campbell, Katrina; Teixeira-Pinto, Armando; Craig, Jonathan C.; Strippoli, Giovanni F.M.
Summary: Background & aims: Dietary and supplemental long chain omega-3 polyunsaturated fatty acids (n-3 PUFA) have shown vascular benefits for the general population, but effects among people with chronic kidney disease (CKD) are largely uncertain. We aimed to evaluate the effects of n-3 PUFA intake among patients with CKD. Methods: We searched MEDLINE, Embase, and CENTRAL through January 12, 2018. Eligible studies were randomized controlled trials evaluating n-3 PUFA intake (supplementation or dietary) compared with placebo, standard care, or other treatment, on cardiovascular and all-cause mortality, end stage kidney disease (ESKD), acute transplant rejection, and allograft loss. Risks of bias and evidence certainty were assessed using Cochrane and Grading of Recommendations Assessment, Development and Evaluation processes. Results: Sixty trials (4129 participants) were eligible, all of supplementation, with a median follow-up of 6 months. Low to very low certainty evidence suggested that n-3 PUFA supplementation reduced cardiovascular death for participants on hemodialysis (39 events; relative risk (RR) 0.45, 95% confidence interval (CI) 0.23–0.89), prevented ESKD (29 events; RR 0.30, CI 0.09–0.98) in participants with CKD not receiving renal replacement therapy, and made little or no difference in all-cause mortality (215 events; RR 1.05, CI 0.84–1.33), acute transplant rejection (188 events; RR 0.98, CI 0.80–1.21) or allograft loss (39 events; RR 0.98, CI 0.54–1.81]). Risk of bleeding (44 events; RR 1.40, CI 0.78–2.49) and gastrointestinal side-effects (103 events; RR 1.14, CI 0.79–1.67) were uncertain. Conclusions: n-3 PUFA supplementation may reduce cardiovascular mortality in patients on hemodialysis but it is uncertain whether supplementation prevents mortality or ESKD in patients with CKD.